Tingkat Pengetahuan Masyarakat Dalam Upaya Mitigasi Bencana Gempa Dan Tsunami Di Kota Pariaman - Marfadila, Engla; Hermon, Dedi; Zuriyeni, Elvi (Pendidikan Geografi, 2013)
This research aimed to get the information, analyze and describe data on the level of public knowledge in an effort to mitigate the earthquake and tsunami in the Pariaman City. 1). Standard Operation Procedure  (SOP) tsunami early warning system, 2). the suitability of placeman of tsunami early warning sirine, 3).  Public knowledge about earthquake and tsunami, 4). Rescue efforts that must be made public when the earthquake and tsunami occurred. This research is a qualitative study using interview techniques. To answer this problem used primary data and secondary data. Primary  data was collected through observation, interview, discussion with informants and documentation are taken in the field, while the secondary data obtained from the relevant parties. The result of this study indicate 1) the disaster agency said that the lack of a tsunami early warning system in the Pariaman city. 2) people said Pariaman sirine for the city is still not suffielent  because the city has only one tsunami early  warning sirine. 3) so far people know enough about the earthquake and tsunami . 4) people already know how to rescue that should  be done when the earthquake and tsunami occurred.